Application of a method for combining measured data and modelling results in air quality assessment in Spain - Martín, Fernando; Palomino, Inmaculada; Vivanco, Marta G. (Física de la Tierra, 2010)
The use of a method to combine air pollution measurements and CHIMERE model data is presented. This method is to response to the European and Spanish regulatory requirements to provide reliable information about the air quality in Spain. The method consists of using linear regression and kriging interpolation to correct the model results improving the fit to the observations. It was separately applied to the rural and urban air pollution yielding maps for each case, which then were combined by taking into account the distribution of rural and urban areas in the domain. The results for the annual mean of PM10 for 2004 in Spain are shown and discussed
Keywords: Air quality; PM10; CHIMERE model; Kriging; Linear regression